“Metastases of Desire” in Andrea Maturana’s Narrative - Candia-Cáceres, Alexis (2023)
In this study, we present an analysis of the representation of eroticism and sexual violence in Andrea Marurana’s narrative: (Des)encuentros (des) esperados (1992), El daño (1997) and No decir (2006). By employing a series of resources drawn from literary theory, gender studies, philosophy and psychology, it is proposed that her writing can be interpreted using the notion of “metastasis of desire”, a concept that accounts for both the transformation and dissemination that desire undergoes in her novels and stories, as well the harmful effects of unethical and illegitimate enjoyment.